The role of attitudes and learning orientation in interdisciplinary learning - Agcaoili, Elicano James Noel (Nanyang Technological University, 2023)
The interdisciplinary learning approach refers to an educational approach that aims to integrate knowledge from across multiple disciplines, and interdisciplinary learning has been an area of interest in the educational space. The present study examined the effect of Learning Orientation and Attitudes Towards Interdisciplinary Learning on Outcome Achievement in interdisciplinary learning. It was hypothesized that Learning Orientation and Attitudes were able to predict Outcome Achievement in interdisciplinary learning, and that Learning Orientation moderated the effect of Attitudes on Outcome Achievement. Questionnaire data was collected amongst undergraduate students about their experiences with learning within an interdisciplinary course (N = 93). The findings suggested that the Learning Orientation variables of Intrinsic (Achievement) Motivation, as well as Performance-Avoidance and Mastery-Avoidance Goal Orientations, were predictors of Outcome Achievement in interdisciplinary learning. However, Attitude Towards Interdisciplinary Learning was not found to be a predictor, and there was no moderating effect of Learning Orientation. Given the popularity of interdisciplinary learning approaches and its increasing implementation, this suggests that a greater focus needs to be placed on psychological factors which can affect the success of interdisciplinary learning. This is especially important for stakeholders to consider the role of Learning Orientation in interdisciplinary learning.